Self-awareness and self-deception: a Sartrean perspective - Neuber, Simone (Continental philosophy review, 2016)
In spite of the fact that many find Jean-Paul Sartre’s account of la mauvaise foi puzzling, unclear and troublesome, he remains a recurring figure in the debate about self-deception. Indeed, Sartre’s exposition of self-deception is as puzzling as it is original. The primary task of my paper will be to expose why this is the case and to thereby correct a recurrent misunderstanding of Sartre’s theory of consciousness. In the end, will we see that Sartre offers the following theory: self-deception is to be accounted for by assuming that there are intrinsically self-deceptive epistemic states. The latter are self-deceptive in so far as they claim certainty while nevertheless being accompanied by an inbuilt and incorruptible awareness of being unwarranted. For Sartre, developing this rather peculiar account of self-deception, is, as we will see, not primarily intended as an end in itself. Rather, Sartre thereby hopes to illuminate the nature of self-awareness as (i.) epistemically super-secure, (ii.) pre-reflexive, (iii.) non-positional and “embryonic” knowledge that (iv.) does not necessitate but can still ground epistemically super-secure reflexive knowledge, and (v.) that can replace Freud’s notion of unconscious knowledge. As an account of self-deception, Sartre’s suggestion, however, comes at a high price. Apart from the presuppositions Sartre makes in the theory of consciousness and intentionality, his account is deflationist with regard to local cases of self-deception.